ANALYSIS OF HOMOMORPHIC ENCRYPTION METHODS IN CLOUD COMPUTING SYSTEMS - Karimov , Abdukodir Abdisalomovich; Olimov , Iskandar Salimboyevich (Innovative Development in Educational Activities, 2023)
This article discusses gamma encryption in detail. In addition, a comparative analysis of commonly used types of gamma encryption, i.e. partially homomorphic and fully homomorphic encryption, is presented. RSA, El-Gamal, Paillier, Goldwasser-Micali, Boneh-Goh-Nissim and Gentry Homomorphic encryption systems were analysed and the results presented.